(untitled) (Modern education and development, 2025)
The current study undertakes a detailed analysis of Khaled Hosseini‟s The Kite Runner representative novel. Hosseini, an Afghan born American writer depicts a war-torn Afghanistan in various universal themes i.e., family re-union, discrimination, regret, childhood, guilt, womanhood, betrayal, religion and salvation that played a considerable role in abating commission of crimes in Afghanistan during pre and post-Taliban periods which ended up shaping the interminable psychological scars of the protagonist. In his work, Hosseini reveals the devastating status of Afghans in general and women and children in particular who have, for decades, been irrationally marginalized and confined to the four walls of their homes by the society. His quests for wealth, love, loyalty and unqualified peace among Afghan citizenry whom he equates to have rights just like other human beings globally is the only means through which the protagonist considers a key to chart out a new future.